Gorilla in the midst auditing to add value - Nicholas and Smith (New South Wales : Nicholas and Smith, 2002)
The role of auditor of management systems has changed significantly and much more is expected of auditors. The trend is towards auditing outcomes rather than only compliance. The focus is on adding value to management systems and to the business overall. This is exemplified in new and revised international standards and in industry standards being adopted worldwide by business.
Keywords: Management; Personnel management